Assessing the Impact of News Reporting Regarding the Mount Semeru Eruption - Betty Gama; Yoto Yoto Widodo; Nunun Tri Widarwati; Henny Sri Kusumawati Kusumawati (Profetik: Jurnal Komunikasi, 2024)
Communication has an important role in supporting the process of education and learning. To make the learning material well transformed for santri (students), an appropriate and effective communication strategy is needed. Thus, this study analyzes communication strategies in empowering entrepreneurship at Pesantren Asshiddiqiyah 2, Tangerang. This is a qualitative study and uses a case study method. Its data was collected by case studies, in-depth interviews and literature studies. Its results reveal that ustadz (teachers) in the pesantren (Islamic Boarding Schools) tend to act more as communicators in entrepreneurship learning. The message packaging strategy, which includes religious lessons, general lessons, entrepreneurship, and life skills, was delivered in three ways. The first is applying the local content curriculum to the formal learning process, the second is integrating entrepreneurship values with extracurricular activities, and the third is conveying a message of independence and responsibility in daily life within the pesantren environment. Meanwhile, the channels used is face-to-face communication and the media. The communicants involved were students of Classes 10, 11 and 12. The effects of the communication process contribute to the domains of cognition, affection, and psychomotor.